Air bubbles in calcium caseinate fibrous material enhances anisotropy. (February 2019) - Wang, Zhaojun; Tian, Bei; Boom, Remko; van der Goot, Atze Jan
Abstract: Dense calcium caseinate dispersions can be transformed into hierarchically fibrous structures by shear deformation. This transformation can be attributed to the intrinsic properties of calcium caseinate. Depending on the dispersion preparation method, a certain amount of air gets entrapped in the sheared protein matrix. Although anisotropy is obtained in the absence of entrapped air, the fibrous appearance and mechanical anisotropy of the calcium caseinate materials are more pronounced with dispersed air present. The presence of air induces the protein fibers to be arranged in microscale bundles, and the fracture strain and stress in the parallel direction are larger compared with the material without air. The effects can be understood from the alignment of the fibers in the parallel direction, providing strain energy dissipation. This study shows that creation of anisotropy is the result of interactions between multiple phases. Graphical abstract: Image 1 Highlights: Air incorporation enhances the anisotropy of sheared calcium caseinate materials. Air incorporation results in a fibrous appearance. Fibrous materials are created in the absence of transglutaminase-induced crosslinking. Air bubbles act as a fracture toughening mechanism in the parallel direction.